ANALISIS KONTRIBUSI KELENTUKAN, KEKUATAN, DAN DAYA TAHAN ATLET GULAT PPLP/D PROVINSI SUMATERA UTARA - Jan Bobby Nesra Barus; Julius Nesra Basgimata Barus; Ketrin Russel Br Tarigan (JURNAL CURERE, 2022)
Wrestling is a martial art that requires extraordinary physical conditions to carry out effective attacks and techniques to defend and bring down opponents. In addition to being in high physical condition during training and competition, many important variables, such as technical training, tactical training, and mental training, must be trained to achieve peak performance. This study aims to determine the contribution of flexibility, strength, and endurance of PPLP/D wrestling athletes in North Sumatra Province. The method used is a survey with test and measurement techniques. The population in this study was PPLP/D Wrestling Athletes totaling 15 athletes, which were taken using purposive sampling technique. Instruments to measure arm muscle strength using the Push Up test, flexibility using the Sit and Reach test, and endurance tests using the Multistage Fitness Test (beep test) have passed the validity and reliability stages of the instrument. Through the prerequisite test stage, the normality test analysis uses Lilliefors and the homogeneity test uses the F-test. The data analysis technique used percentage (%). The results showed that the strength of the PPLP/D wrestling athletes of North Sumatra Province was in the "good" category, the flexibility of the Bantul gym wrestling athletes was in the "less" category, and the endurance of the PPLP/D wrestling athletes of North Sumatra Province was in the "good" category. So that aspects of strength and endurance contribute to PPLP/D wrestling athletes in North Sumatra Province, while aspects of flexibility contribute to PPLP/D wrestling athletes in North Sumatra Province.